Adverse perception of cough in patients with severe asthma: a discrete choice experiment - Joshua Holmes; Vikki O'Neill; Lorcan P. McGarvey; Liam G. Heaney (ERJ Open Research, 2023)
Background Asthma symptoms adversely impact quality of life in particular in those with poor disease control. Commonly used patient-reported measures for asthma used to assess asthma control often inadequately capture the impact of cough, despite evidence that cough is one of the most bothersome symptoms for patients with asthma. This study aims to improve our understanding of how patients with asthma perceive cough to better understand its clinical impact. Methods A discrete choice experiment (DCE) was performed in two distinct adult asthma populations; those with severe asthma as defined by Global Initiative for Asthma (GINA) step 4/5 classification and those with moderate asthma (a GINA steps 2 or 3 classification of asthma severity). Results Choices were highly dominated by the cough attribute in the symptoms complexes; 48.4% of patients with severe asthma and 31.3% with moderate asthma consistently chose the alternative with the lowest level of cough. Furthermore, cough predominance was found to be significantly associated with severity of asthma (p=0.047). Patients with moderate asthma were not willing to accept any additional symptoms to reduce cough from severe to mild. However, these patients were willing to accept mild breathlessness, mild sleep disturbance, severe chest tightness and severe wheezing to remove coughing altogether. Conclusions Patients with asthma prefer to have less cough and are willing to accept greater levels of other symptoms to achieve this. Additionally, asthma severity may influence an individual's perception of their symptoms; cough is a more important symptom for patients with severe asthma than those with a milder disease.